Religion and the New Technologies - Noreen Herzfeld (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
In April 2000, Bill Joy, co-founder and chief scientist at Sun Microsystems published a controversial article entitled "Why the Future Does not Need Us." Joy called for a moratorium on research in three new technological fields-artificial intelligence, nanotechnology, and genetic engineering. He noted that, while we were poised to make rapid technological advances in each of these areas, our understanding of the ethical questions these technologies would inevitably raise was lagging far behind. The intervening years since Joy's warning have indeed brought significant advances in each of these fields, advancements that have huge implications for how human life will unfold. Each holds great promise-for new medical cures, for new materials and machines, and for new insights into our world. However, each of these technologies also brings the possibility of great peril. For good or ill, these technologies will change the way we work, live, think, and love. Thus, it makes sense to approach them from a religious perspective. How do these new technologies change our understanding of ourselves, our place in the world, our relationships to one another, the way we face death, or our relationship to God?